Calibrating temper loss severity in the transition to toddlerhood: Implications for developmental science. Issue 4 (2nd October 2022) - Krogh-Jespersen, Sheila; Kaat, Aaron J.; Petitclerc, Amelie; Perlman, Susan B.; Briggs-Gowan, Margaret J.; Burns, James L.; Adam, Hubert; Nili, Amanda; Gray, Larry; Wakschlag, Lauren S.
Abstract: The integration of neurodevelopmental perspectives into clinical science has identified irritability as an early dimensional marker of lifespan mental health risk. Elucidating the developmental patterning of irritable behavior is key to differentiating normative variation from risk markers. Accounting for dysregulation and contextual features of irritability is useful for differentiation at preschool age, laying the groundwork for even earlier characterization. We provide initial evidence for the validity of the Multidimensional Assessment Profile of Disruptive Behavior Temper Loss Scale, Infant-Toddler version in two independent samples of 12-18-month-olds from the US. We calibrated the measure using item response theory in a large representative sample, then validated within an independent sample. We characterized the developmental patterning of irritable behaviors and their dimensional spectrum, and demonstrated test-retest reliability, and convergent validity. The MAP-DB-IT is a standardized, dimensional survey assessing irritability that serves as a tool for characterizing the developmental expression of early mental health risk.